Deep reinforcement learning hands-on : apply modern RL methods to practical problems of chatbots, robotics, discrete optimization, web automation, and more /: apply modern RL methods to practical problems of chatbots, robotics, discrete optimization, web automation, and more. (2020) - Lapan, Maxim
No abstract available